Study on the performance of Type II vertical rescue timber shores based on experiment and simulation - Feng Zhang; Xiangyang Lu; Hao Zhang (PLoS ONE, 2025)
Structural instability poses significant risks at earthquake rescue sites, where Type II vertical timber shores play a pivotal bridging role in rapidly securing operational space safety. To systematically evaluate their structural performance and failure mechanisms, this study employed a self-developed hydraulic testing apparatus to conduct compressive bearing capacity tests on three Type II vertical shore configurations: Double T-A, Double T-B, and Two-Post. Vertical downward displacement-controlled loading was applied until failure. Concurrently, refined finite element models incorporating key joint contact characteristics (wedges, plywood gussets, nails) were established using Abaqus software for numerical simulation. Experimental and simulation results demonstrated strong agreement, revealing that: The Two-Post shore exhibited the highest ultimate bearing capacity (239.0 kN), significantly outperforming the Double T-B (200.8 kN) and Double T-A (190.9 kN) types. Failure was typically preceded by audible cracks from wedge cracking, plywood gusset expansion, and buckling of posts near the mid-span. The yield point was identified on the load-displacement curves via the farthest point method. Integrating the Allowable Stress Design (ASD) method and site-specific human-machine-environment factors (psychological impact coefficient C p , wood moisture defect coefficient C m , load duration coefficient C d ), a safety factor K = 2.0 is proposed for calculating the design bearing capacity ( F d = F u / 2.0). This research elucidates the failure mechanism of Type II vertical timber shores, confirms the superiority of the Two-Post configuration, emphasizes the critical influence of load centering on support effectiveness, and provides essential experimental data and a theoretical basis for the safe design and application of timber shoring systems in earthquake rescue operations.